Analisis Efektivitas Mesin Stamping melalui Pendekatan Overall Equipment Effectiveness (OEE) dan Six Big Losses di PT. XYZ - Sudarsono Aldi; Tri Ngudi Wiyatno; Fibi Eko Putra (Jurnal Multidisiplin Indonesia, 2026)
The increasingly competitive manufacturing industry requires companies to continuously improve productivity, efficiency, and product quality. One of the key factors in achieving production targets is the effective utilization of machines as major assets in the manufacturing process. PT. XYZ is a manufacturing company that uses a Stamping machine as its main production equipment; however, it still experiences several problems such as unexpected breakdowns, long die setup time, reduced production speed, minor stoppages, and defective products, causing production targets to be unmet optimally. This study aims to analyze the effectiveness level of the Stamping machine using the Overall Equipment Effectiveness (OEE) method, identify the components of availability, performance, and quality, and determine the dominant production losses through Six Big Losses analysis. The study was conducted from June to October 2025 using downtime, operating time, production output, and reject product data. The results showed that the average OEE value of the Stamping machine was 74.05%, which is still below the world-class standard of 85%. The availability value was 84.29%, performance was 90.13%, and quality was 97.44%. The largest losses were Breakdown Losses at 28.85%, Setup and Adjustment Losses at 16.43%, and Idling and Minor stoppages at 12.02%. Improvement proposals through preventive maintenance, autonomous maintenance, SMED implementation, 5S program, operator training, and daily inspections are projected to increase the OEE value to 82.15%.